The Comparative Study About Intellectual Property Rights And The Transfer Of Land Rights For The Development Of Indonesia Land Law - Yazid Fatoni; Adi Sulistiyono; Lego Karjoko (Unram Law Review, 2023)
The transfer of land rights is a classic problem whose implementation is often uncertain. In the framework of alternative material for developing national land law, this article will try to compare the transfer of land rights with the transfer of Intellectual Property Rights. The method in this article is a normative legal research method with a comparative law approach as the primary approach. In the transfer of land rights, at least several types of law are used as a component in assessing their validity. When compared to the transfer of Intellectual Property Rights, an Intellectual Property Right must be registered for protection, as well as when the Intellectual Property Right is transferred. Regulations in Intellectual Property Rights are more specific because they are under specific statutory law and through a registration mechanism. The transfer of land rights seen from the perspective of Law Number 5 of 1960 concerning Basic Agrarian Regulations or what is often referred to as UUPA (Basic Agrarian Law) and Government Regulation Number 24 of 1997 concerning Land Registration does require land registration, but that does not mean that land that is not registered does not get protection, this also implements in the transfer of land rights. Even though the transfer of land rights does not use the mechanisms and conditions specified in Government Regulation Number 24 of 1997, the transfer of land rights under the main provisions in customary law is still recognized. It is usually implemented when the dispute goes to court.